Optimization Of Fat Suppression Techniques Using Dixon And Application In MRI Examination - Wahdini Hanifah; Fatimah Fatimah; Marichatul Jannah (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
ABSTRACTMagnetic resonance imaging has been used to detect and assess the presence and extent of fat accumulation. Dixon technique has been used clinically to achieve fat suppression through different presession frequencies of fat and water protons. Dixon, allows the contribution of fat signals to be suppressed in post-processing rather than during acquisition, as well as providing a map of the distribution of water and fat. The aims of this study is to analyze the role of Dixon techniques on fat suppression or fat quantification. Evaluated its advantages in performing fat suppression, reducing artifacts, and describing Dixon's application on MRI examination. Literature review was conducted to analyze the effectiveness, role, and advantages of Dixon techniques in MRI examinations. Articles are selected based on inclusion criteria. Each article is qualitatively analyzed and explained descriptively. The results show that Dixon technique can be combined with several sequences, including gradient echo or fast spin echo. Scanning with Dixon sequences, namely 2-point Dixon, 3-point Dixon, 6-point Dixon and multi-point Dixon. Dixon technique used provides better fat suppression even in areas where other techniques fail for technical reasons. The uniformity of Dixon's technique in suppressing fat signals is significantly higher. Dixon technique plays an excellent role in MRI imaging of the head and neck, musculoskeletal, abdominal and breast. In conclusion, Dixon technique has been proven to be able perform fat suppression more effectively on MRI examination. In its application, Dixon can shorten the scanning time, thereby reducing the risk factor for sedation, especially for children.ABSTRAKMagnetic Resonance Imaging telah digunakan untuk mendeteksi dan menilai keberadaan dan tingkat akumulasi lemak. Teknik Dixon telah digunakan secara klinis untuk mencapai penekanan lemak melalui frekuensi presesi yang berbeda dari proton lemak dan air. Dixon memungkinkan kontribusi sinyal lemak ditekan dalam pasca-pemrosesan daripada selama akuisisi, serta menyediakan peta distribusi air dan lemak. Tujuan dari penelitian ini adalah untuk menganalisis peran teknik Dixon terhadap penekanan lemak atau kuantifikasi lemak. Mengevaluasi keuntungannya dalam melakukan penekanan lemak, mengurangi artefak, dan menggambarkan aplikasi Dixon pada pemeriksaan MRI. Literature review dilakukan untuk menganalisis efektivitas, peran, dan keunggulan teknik Dixon dalam pemeriksaan MRI. Artikel dipilih berdasarkan kriteria inklusi. Setiap artikel dianalisis secara kualitatif dan dijelaskan secara deskriptif. Hasil penelitian menunjukkan bahwa teknik Dixon dapat dikombinasikan dengan beberapa urutan, termasuk gradient echo atau fast spin echo. Pemindaian dengan urutan Dixon, yaitu 2-point Dixon, 3-point Dixon, 6-point Dixon dan multi-point Dixon. Teknik Dixon yang digunakan memberikan penekanan lemak yang lebih baik bahkan di daerah di mana teknik lain gagal karena alasan teknis. Keseragaman teknik Dixon dalam menekan sinyal lemak secara signifikan lebih tinggi. Teknik Dixon memainkan peran yang sangat baik dalam pencitraan MRI kepala dan leher, muskuloskeletal, perut dan payudara. Kesimpulannya, teknik Dixon telah terbukti mampu melakukan penekanan lemak dengan lebih efektif pada pemeriksaan MRI. Dalam penerapannya, Dixon dapat mempersingkat waktu pemindaian, sehingga mengurangi faktor risiko sedasi, terutama untuk anak-anak.